Decentralization of urban development in Southeast Asia: comparative notes and research questions. - Samarudin Rejab, (Universiti Kebangsaan Malaysia, 1978)
National development in South-East Asia today has been accompanied by the emergence of developed urban centers as a significant element in the national system of cities. Besides the drastic urban growth due to natural increases in population and process of urbanization, the development of these cities ironically continue to enhance primacy which to a large extent contradicts urban policy efforts to create a balanced national system of cities. Their dominance is a consequence rather than the cause of centralization or over concentration of urban functions, policy decisions, city-size distribution and basic resources. Even the regionalized growth pole strategy seems to play a supplementary role in their predominance. So various comparative notes and research questions are highlighted to expose another namely decentralization. Specific focus would be given to various policy views and emerging alternative options. The trend in major South-East Asian cities shows little change despite concerned redistribution goals and regional equality. The general conclusion is that new planning alternatives as well as fruitful research have to be undertaken.